2021
DOI: 10.1021/acssuschemeng.1c01055
|View full text |Cite
|
Sign up to set email alerts
|

Development of High-Molecular-Weight Fully Renewable Biopolyesters Based on Oxabicyclic Diacid and 2,5-Furandicarboxylic Acid: Promising as Packaging and Medical Materials

Abstract: Renewable and biodegradable linear polyesters with oxabicyclic units based on the ring-opening polymerization (ROP) have attracted considerable interest as alternatives to petrochemical-based polyesters. However, incorporating bio-based aromatic building blocks into the linear polyesters with oxabicyclic units by the ROP process is limited. Herein, we report three series of oxabicyclic renewable polyesters based on oxabicyclic diacid (OBDA), monomethyl oxabicyclic diacid (MBDA), and oxabicyclic anhydride with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 55 publications
0
21
0
Order By: Relevance
“…In the latter polymer, ether linkages are thought to be responsible for increasing chain flexibility and decreasing crystallinity, leading to a higher gas permeation. , The presence of an oxygenated heterocycle moiety in poly­(2a)-H , disrupting chain packing, is most likely to have the same effect here and cause poly­(2a)-H to have slightly increased permeability values relative to lcAPES PES-X,5 (X = 10–16) reported by Zhou et al (0.6–1.0 barrer) . Despite having slightly higher permeability values than other bioderived polymers, including outside the lcAPES category, there might be a potential to further increase barrier properties of this polymer through processing, by orientating polymer chains to reduce the free volume and enhance crystallinity. An alternative approach could involve the removal of some isopropylidene groups from the xylose cores, so as to induce intermolecular hydrogen bonding and increase crystallinity. , …”
Section: Resultsmentioning
confidence: 99%
“…In the latter polymer, ether linkages are thought to be responsible for increasing chain flexibility and decreasing crystallinity, leading to a higher gas permeation. , The presence of an oxygenated heterocycle moiety in poly­(2a)-H , disrupting chain packing, is most likely to have the same effect here and cause poly­(2a)-H to have slightly increased permeability values relative to lcAPES PES-X,5 (X = 10–16) reported by Zhou et al (0.6–1.0 barrer) . Despite having slightly higher permeability values than other bioderived polymers, including outside the lcAPES category, there might be a potential to further increase barrier properties of this polymer through processing, by orientating polymer chains to reduce the free volume and enhance crystallinity. An alternative approach could involve the removal of some isopropylidene groups from the xylose cores, so as to induce intermolecular hydrogen bonding and increase crystallinity. , …”
Section: Resultsmentioning
confidence: 99%
“…Weinberger et al [ 118 ] investigated the PEF enzymatic degradation and found that the influence of particle size became smaller when the molecular weight was higher and they optimized the hydrolysis conditions such as in the 1 M phosphate buffer, pH 8, at 65 °C with Humicola insolens , where PEF reached 100% hydrolysis. Zhou et al [ 119 ] synthesized a series of biodegradable polyesters with FDCA, BDO, and oxabicyclic units via ROP. The polyesters obtained showed biodegradability within seven days with less than 30 mol% FDCA units.…”
Section: Co-polyesters From Fdcamentioning
confidence: 99%
“…Kinetically blocking the reverse DA process is also ac ommonly employed strategy that suits certain synthetic applications.M ethods include hydrogenation of the alkene bond in the adducts (92), [64,132] or alkene epoxidation/dihydroxylation (93). [133,134] In addition, synthetic manipulation of the oxanorbornene exocyclic groups is another means to tune the cycloreversion rate (Scheme 14). [135] This can be conveniently done for instance via redox transformations,f or example by reduction of the anhydride functionality in the adduct 89 and functionalization to 94 a-c as shown in the example in Scheme 14.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…Kinetically blocking the reverse DA process is also a commonly employed strategy that suits certain synthetic applications. Methods include hydrogenation of the alkene bond in the adducts ( 92 ), [64, 132] or alkene epoxidation/dihydroxylation ( 93 ) [133, 134] . In addition, synthetic manipulation of the oxanorbornene exocyclic groups is another means to tune the cycloreversion rate (Scheme 14).…”
Section: Overcoming Unfavorable Thermodynamics: Tandem Reactionsmentioning
confidence: 99%